Ritualità organiche come espedienti per una trasformazione universale - De Simone , Angela Anna (TransCulturale, 2024)
The transformative practices proposed are silence, breathing, eating and walking. The dimension of silence leads man to the ἐποχή, to empty freedom, while Anapanasati and Prāṇāyāma lead to the contemplation and rhythmization of breathing. The ritual of eating shows us the meeting of life and death, while the walk shows us the abyss of the present. All these rituals aim to re-orientate contemporary man through the recognition of the value-Transcendence.